COMPUTER MODELING OF ACCURACY CHARACTERISTICS OF STRAPDOWN INERTIAL NAVIGATION SYSTEM - Mukhina, M. P.; Filyashkin, M. K. (Radio Electronics, Computer Science, Control, 2019)
Context. The problem of correction for operation of strapdown inertial navigation system used for unmanned aerial vehicle is urgent because of further increased requirements to autonomous flight in blackout zones. The object of the study was to simulate the accuracy characteristics of strapdown inertial navigation system based on known (or given) instrument errors of its sensors. Objective. The goal of the work is to develop a mathematical and computer model of the strapdown inertial navigation system and estimate its accuracy characteristics based on given values of sensor errors. Method. The mathematical and computer models of the strapdown inertial navigation system based on slow, medium and fast cycles are developed. For the simulation of accuracy characteristics, the strapdown inertial navigation system is represented as a set of dynamic and kinematic equations in local tangent plane coordinate system with the Earth’s model taking into account components of gravity acceleration. The models of sensors are developed based on characteristics of low-cost microelectromechanical sensors used onboard. Data fusion algorithms were previously considered and include modified Kalman filter or, for some cases, complimentary filter by compensation scheme, but not considered here in details. Direction cosine matrix for strapdown inertial navigation system algorithms is found by Poisson’s method. Results. The developed models have been realized and simulated in MATLAB+Simulink. Initial parameters (errors of the primary information sensors and the flight conditions) during simulation have been varied: medium, high and low latitudes; direction of flight (along and across the meridian; on and against the direction of rotation of the Earth). Conclusions. The developed models and their simulations have been compared with actual testing results of strapdown gyrovertical СБКВ-П2А and confirmed the validity. It allow us to recommend them for use in designing strapdown inertial navigation system of unmanned aerial vehicle, as well as for experimental study of innovative data fusion algorithms for integrated satellite and inertial navigation system.